Peneladanan Allah: Perbandingan antara Herman Bavinck dan Mazmur 1 - Novan (Verbum Christi: Jurnal Teologi Reformed Injili, 2025)
This paper aims to compare and contrast the differences and similarities between Herman Bavinck's views and those presented in Psalm 1, particularly focusing on the concept of imitating God as it relates to the image of God, the imitation of Christ/God, and its implications for life in this world. The method used is a literature study presented with a qualitative-comparative approach. It can be concluded that Herman Bavinck and Psalm 1 both affirm that the image and imitation of God are essential to ethical transformation and spiritual flourishing. However, they approach the subject from different theological foundations and modes of application. Bavinck, through a Christocentric and Reformed lens, emphasizes that the image of God, though damaged by sin, is restored in union with Christ, leading to a life of obedience, self-denial, and virtue. Psalm 1, on the other hand, presents imitation through Torah meditation, fostering a righteous and fruitful life marked by justice and covenantal faithfulness. While Bavinck focuses on Christ as the model for restoration, Psalm 1 highlights Scripture’s formative power. Both agree, however, that true imitation of God brings inward renewal and outward transformation shaped by divine guidance.